Phosphorus levels for growing and finishing swine - G L Allee; B A Koch; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1974)
To determine the minimal level of supplemental phosphorus required by growing pig, ninety pigs averaging 34 pounds were randomly assigned from outcome groups to 18 pens representing three replications of six dietary treatments. Graded levels of supplemental phosphorus (0, 0.05, 0.10, 0.15, and 0.20% of the diet) from dicalcium phosphate were added to a 16% protein milo-soybean meal basal diet containing 0.36% phosphorus. Additionally, meat and bone meal was also evaluated as a phosphorus source. For the first four weeks of the trial (Phase I), daily gains were maximized at 0.15% supplemental phosphorus, or a total phosphorus level of 0.51% of the diet. Similarly, during Phase II of the trial (pigs weighing 70 to 220 lbs.) daily gains were maximized at 0.15% supplemental phosphorus. Results suggest that growing and finishing pigs should be supplied at least 0.15% supplemental phosphorus from an available source, such as dicalcium phosphate and demonstrated that 5% meat and bone meal in the diet of the growing pig will supply the needed supplemental phosphorus.; Swine Day, Manhattan, KS, November 14, 1974
Keywords: Swine day; 1974; Kansas Agricultural Experiment Station contribution; no. 483; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 221; Swine; Phosphorus; Growing swine; Finishing swine